2007
DOI: 10.1071/ea04222
|View full text |Cite
|
Sign up to set email alerts
|

Survey of feral honey bee (Apis mellifera) colonies for Nosema apis in Western Australia

Abstract: The parasite, Nosema apis, was found to be widespread among feral populations of honey bees (Apis mellifera) in the south-west of Western Australia. The location, month of collection and whether the feral colony was enclosed in an object or exposed to the environment, all affected the presence and severity of infection. There was no significant difference in the probability of infection between managed and feral bees. However, when infected by N. apis, managed bees appeared to have a greater severity of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
2
7
1
Order By: Relevance
“…ceranae was present in the Australian populations [ 66 ]. Our pathogen results are consistent with studies that identified lower intensity or prevalence of Nosema parasites in feral bees than managed bees in the U.S. and Australia [ 22 , 67 , 68 ], and a similar trend in Europe [ 21 ]. We detected an extraordinarily high prevalence of N .…”
Section: Discussionsupporting
confidence: 92%
“…ceranae was present in the Australian populations [ 66 ]. Our pathogen results are consistent with studies that identified lower intensity or prevalence of Nosema parasites in feral bees than managed bees in the U.S. and Australia [ 22 , 67 , 68 ], and a similar trend in Europe [ 21 ]. We detected an extraordinarily high prevalence of N .…”
Section: Discussionsupporting
confidence: 92%
“…virus infections and EFB infections (brood disease) are more prevalent but data suggests no significant difference in N. ceranae prevalence, Table I). This is congruent with data from A. mellifera where brood disease is very low in free-living colonies and significantly higher in managed colonies (Goodwin et al 1994;Hornitzky et al 1996), whereas N. apis infections show little difference in incidence between managed and free-living colonies (Manning et al 2007). Although the number of samples from wild colonies is low (N =8), our data suggest that the negative impact of apiculture on disease prevalence is similar in both A. mellifera and A. cerana .…”
Section: Discussionsupporting
confidence: 90%
“…Incidentally, this region of the USA suffered one of the most devastating droughts recorded in recent history in 2011 (Combs 2012), which likely influenced the colony-level dynamics of Nosema in feral honey bees at the WWR for our 2013 sampling period. More studies are needed to determine the seasonal changes in Nosema levels in this population during the entire year, particularly Prevalence of Nosema in feral honey bees 567 in the fall, and if the likelihood of Nosema infection is correlated with weather, as was found previously in other regions (Doull and Cellier 1961, Cantwell and Shimanuki 1970, Manning et al 2007. Such studies have shown that Nosema levels are lowest during the summer months, while they go up in spring or autumn (Doull and Cellier 1961, Manning et al 2007).…”
mentioning
confidence: 99%
“…Manning et al (2007) reported high levels of N. apis infection in feral honey bee colonies around southwestern Australia from 2002 to 2003. While all the colonies surveyed were infected with N. apis , the presence and severity of infection were significantly affected by the location of the colony and the weather during sample collection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation